Comparison of Nutritional and Meat Quality Characteristics between Two Primal Cuts from Aceh Cattle in Aceh Province, Indonesia - Hamny Sofyan; Aryani Sismin Satyaningtijas; Cece Sumantri; Etih Sudarnika; Srihadi Agungpriyono (Veterinary Medicine International)
The Aceh cattle are local Indonesian beef cattle that are farmed in Aceh Province. This type of cattle is one of the sources of meat for the Aceh people. This study aims to analyze the quality of two primal cuts (longissimus lumborum and semitendinosus muscle) from Aceh cattle based on the muscle microstructure characteristics and MSTN gene expression. This study used a sample of longissimus lumborum and semitendinosus muscles from 18 adult male Aceh cattle with the age of 2–2.5 years and a BCS of 3.24. Muscle samples were obtained shortly after the cattle were slaughtered in slaughterhouses in Banda Aceh and Aceh Besar districts. Muscle microstructure analysis was performed using the HE, Masson’s trichrome, and immunohistochemistry staining methods, while the MSTN gene expression analysis was performed using the qPCR method. The analysis of the physical quality of meat includes pH, meat color, fat color, cooking loss, water holding capacity, and WBSF value. The results showed that the area of LL muscle fibers was smaller than that of ST with relatively the same diameter. Both muscles were dominated by fast fibers with a percentage of 82.37% (LL muscle) and 91.80% (ST muscle). The area and composition of the type of muscle fibers are the main factors that influence the tenderness of Aceh beef. A higher distribution of collagen was found in ST muscles than in LL muscles. MSTN gene expression in both muscle types was relatively the same. Aceh cattle have large muscle fibers and are dominated by fast fibers with a high percentage, resulting in a low level of the tenderness of Aceh beef. However, the level of tenderness of Aceh beef is still in accordance with the cooking preparation of original and favorite cuisine of Aceh people.